The Changing Scenario of the Consumption Pattern of Employed People - Darling Selvi, V. (Indian Journal of Marketing, 2006)
India is a developing country, but over the last decade it has witnessed a high GDP growth as well as a decline in population growth. Growth has averaged 6.2% per annum since 1994 while the population growth rate has declined from about 2.1% in the early nineties to around 1.7% during 2004. These two factors have allowed the highest increase in per capita income in the country’s history. This has had a very interesting "income" and "substitution" effects on consumer behaviour. According to official household surveys, the proportion of population below the poverty line fell from 51.3% in 1978 to 36% in 1994 and further to 26.1% in 2000. The purchasing behaviour of people is highly influenced by the changing life styles, standard of living, modernization and growing employment opportunities. The increase in per capita income is increasing the level of consumption expenditure and equally importantly, changing the consumption basket itself. As one may expect, with households becoming wealthier they have shifted away from satisfying basic needs to non-essentials. Hence, this study is an attempt of studying the consumption pattern of fifty employed people in Kanyakumari District.